FRI0522 Vitamin d supplementation improves depression in knee osteoarthritis patients over 24 months. (12th June 2018) - Zheng, S.; Tu, L.; Cicuttini, F.; Han, W.; Zhu, Z.; Antony, B.; Wluka, A.; Winzenberg, T.; Aitken, D.; Blizzard, L.; Jones, G.; Ding, C.
Abstract : Background: Although depression is prevalent in osteoarthritis (OA) patients and the positive association between vitamin D deficiency and depression has been demonstrated, no study has examined the effect of vitamin D supplementation on depression in OA patients. Objectives: To determine the effect of vitamin D supplementation and maintaining sufficient serum vitamin D on depression in patients with knee OA and vitamin D deficiency. Methods: Participants with symptomatic knee OA and vitamin D deficiency were enrolled in a randomised, placebo-controlled trial and received 50, 000IU vitamin D3 (n=209) or placebo (n=204) monthly for 24 months. Serum 25-hydroxyvitamin D [25(OH)D] was measured at baseline, month 3 and 24. Depression was measured using the patient health questionnaire (PHQ-9), and knee symptoms were assessed using Western Ontario and McMaster Universities Arthritis Index (WOMAC) at baseline, month 3, 6, 12 and 24. Multilevel mixed-effect models were used to estimate the association between exposures and outcomes adjusting for potential confounders. Results: Over 24 months, 340 participants (82.3% retention rate) completed the study. The prevalence and incidence of depression were 25.4% and 11.2%, respectively. Depression improved more in the vitamin D supplementation group (β: −0.45, 95% CI: −0.84 to −0.07) compared to the placebo group (β: 0.21, 95% CI: −0.19 to 0.61) (p = 0.02) and in those participants who maintained vitamin D sufficiency (β: −0.44, 95% CI: −0.88 to −0.00) compared to those who did not maintain sufficiency (β: 0.40, 95% CI: −0.18 to 0.97) (p=0.02) over 24 months. Conclusions: These findings suggest that vitamin D supplementation and maintaining sufficient vitamin D levels over 24 months may have beneficial effects on depression in patients with knee OA. References: [1] Stubbs B, Aluko Y, Myint PK, et al. Prevalence of depressive symptoms and anxiety in osteoarthritis: a systematic review and meta-analysis. Age Ageing2016;45(2):228–35. doi:10.1093/ageing/afw001 [2] Anglin RE, Samaan Z, Walter SD, et al. Vitamin D deficiency and depression in adults: systematic review and meta-analysis. Br J Psychiatry2013;202:100–7. doi:10.1192/bjp.bp.111.106666 Acknowledgements: We specially thank the participants who made this study possible, and we gratefully acknowledge the role of Vitamin D Effect on Osteoarthritis Study staff and volunteers in collecting the data. Disclosure of Interest: None declared